A Hubungan Agama dan Negara dalam Perspektif Sejarah Hukum - Atma Hajri, Wira; nufus, hayatun; Bur , Arifin; diansyah, Ar (UIR Press, 2024)
Abstract : The relationship between religion and the state in Indonesia is always interesting to discuss even though the First Principle of Pancasila explicitly mentions